THE ANALYSIS OF COMPLIANCE OF GROUND SUPPORT EQUIPMENT (GSE) PESONNEL TO FLIGHT SAFETY - Dena Piscarini, Amelia; Suryono, Wiwid; Iswahyudi, Prasetyo (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Sultan Hasanuddin International Airport Makassar is operated by PT Angkasa Pura I as the HUB of eastern Indonesia. By having heavy traffic, as an aviation service provider, it should provide excellent service and pay attention to safety and order, one of which is on the air side. Although there is already a Standard Operating Procedure (SOP) in place, there are still violations that occur, namely the lack of compliance of Ground Support Equipment (GSE) personnel with the implementation of Standard Operating Procedures (SOP). The purpose of this study is to determine the level of compliance of Ground Suppoprt Equipment (GSE) personnel and also to find out how to improve the compliance of Ground Support Equipment (GSE) personnel to comply with Standard Operating Procedures (SOP). This research uses quantitative descriptive methods with data collection techniques using observation, questionnaires and literature studies. The analysis method used is the Pearson product moment correlation method. The results of this study indicate that the compliance of Ground Support Equipment (GSE) personnel is still less compliant or not in accordance with Standard Operating Procedures (SOP), namely the unorderly placement of Ground Support Equipment (GSE), less compliant in turning on the rotary lamp when operating Ground Support Equipment (GSE) and there is still Foreign Object Debris (FOD) found on the Apron. And there is a relationship between compliance of Ground Support Equipment (GSE) personnel to flight safety as measured using the Pearson product moment correlation test of 0.9